The triviality and non-triviality of Lambda-Phi-4 model in different spacetime dimensions - Foong, See Kit. (2012)
Our research is an attempt to resolve the triviality status of the Lambda-PHI-4 model in 4-dimensions. The dynamics of the real valued scalar field PHI of the Lambda-PHI-4 model in d-dimensional Euclidean space is described by the action